2014
DOI: 10.1109/tdei.2014.6832257
|View full text |Cite
|
Sign up to set email alerts
|

Streaming electrification of mineral insulating oil and synthetic ester MIDEL 7131

Abstract: Determining the Electrostatic Charging Tendency (ECT) level of insulating liquids requires no large and therefore costly transformers or modelling systems. Small laboratory systems are characterised by simple design and methodology, low volume of liquid sample required for testing, low cost of construction and the following tests. This also applies to pipe flow systems. This paper presents comparative studies of the phenomenon of streaming electrification of mineral TRAFO EN insulating oil and MIDEL 7131 ® syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…It is evident that the ester liquid has a higher leakage current than the mineral oil. Similar findings have also been identified in previous studies [9][10][11]. The different streaming electrification characteristics of the two liquids have been linked to the differences in the liquids' chemistry [13].…”
Section: Influence Of Agingsupporting
confidence: 88%
See 1 more Smart Citation
“…It is evident that the ester liquid has a higher leakage current than the mineral oil. Similar findings have also been identified in previous studies [9][10][11]. The different streaming electrification characteristics of the two liquids have been linked to the differences in the liquids' chemistry [13].…”
Section: Influence Of Agingsupporting
confidence: 88%
“…Thus it is significant to study the streaming electrification behaviors of the ester liquids. Up to now, a few publications have revealed that the ester liquids generally have a higher electrostatic charging tendency than the mineral oil [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Combining with the comparative result between the calculated value of ρ (1) and the accumulated real value of ρ , the GM (0, 2) model of the electrification degree of oil flow and the electrostatic current could be initially expressed as in (5). The data of the electrification degree of the oil flow calculated from the linear regression model is also showed in Table 2.…”
Section: Formula ρmentioning
confidence: 99%
“…The Electrification Degree of oil flow, namely the Charging Tendency, or Electrostatic Charging Tendency (ECT), represents the capability of generating electric charge when the transformer oil flows through the solid insulation surface under certain external conditions such as velocity of flow and pressure, and can be represented by charge density (ρ), which means the charge number generated from per unit volume of transformer oil: ρ= q/V (V is the total volume of transformer oil, and q is the total charge number generated when oil flows through the solid insulation surface). And we often use C/m 3 , pC/ml or pC/cm 3 as the unit of Electrification Degree [1][2][3][4][5][6]. Through researches, scholars from all over the world hold the opinion that the electrification of transformer oil flow has a lot to do with the insulation structure of the transformer, oil flow velocity, oil temperature and charging tendency (electrification degree) of oil flow.…”
Section: Introductionmentioning
confidence: 99%
“…Another action, which should be taken mainly by the users of such equipment, is proper operation supplemented with monitoring of the key apparatus of the system. In the case of power transformers, solid and liquid insulation, which so far has been made of cellulose impregnated with mineral insulating oil will be more often substituted with synthetic insulation, mostly made of aramid papers ultimately impregnated with environment-friendly synthetic and natural esters [1][2][3][4][5][6]. Compared with cellulose, the application of aramids causes a significant increase in the resistance to high temperatures, which is presently the main factor having influence on premature aging of insulation [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%